Food Abundance Is the Main Determinant of High-Altitude Range Use in Snub-Nosed Monkeys - Cyril C. Grueter; Dayong Li; Baoping Ren; Zuofu Xiang; Ming Li (International Journal of Zoology)
High-altitude dwelling primates have to optimize navigating a space that contains both a vertical and horizontal component. Black-and-white or Yunnan snub-nosed monkeys (Rhinopithecus bieti) are extreme by primate standards in inhabiting relatively cold subalpine temperate forests at very high altitudes where large seasonal variation in climate and food availability is expected to profoundly modulate their ranging strategies so as to ensure a positive energy balance. A “semi-nomadic” group of R. bieti was followed for 20 months in the montane Samage Forest, Baimaxueshan Nature Reserve, Yunnan, PRC, which consisted of evergreen conifers, oaks, and deciduous broadleaf trees. The aim of this study was to disentangle the effects of climate and phenology on patterns of altitudinal range use. Altitude used by the group ranged from a maximum of 3550 m in July 2007 to a minimum of 3060 m in April 2006. The proportional use of lichen, the monkeys’ staple fallback food, in the diet explained more variation in monthly use of altitudes than climatic factors and availability of flush and fruit. The abundance of lichens at high altitudes, the lack of alternative foods in winter, and the need to satisfy the monkey's basal energetic requirements explain the effect of lichenivory on use of altitudes.